Cardiometabolic risk factors and early indicators of vascular dysfunction: a cross-sectional cohort study in South African adolescents. Issue 3 (17th March 2021) - Letswalo, Boitumelo Prescilla; Schmid-Zalaudek, Karin; Brix, Bianca; Matjuda, Edna Ngoakoana; Klosz, Fabian; Obernhumer, Natalie; Gaisl, Michael; Engwa, Godwill Azeh; Sewani-Rusike, Constance; Fredriksen, Per Morten; Nkeh-Chungag, Benedicta; Goswami, Nandu
Abstract : Objectives: Prevalence of child and adolescents' overweight and obesity in low- and middle-income countries has increased dramatically. Simultaneously, the incidence of pre-hypertension/hypertension is also increasing in children, which, in turn, predisposes these children to the risk of cardiovascular disease (CVD) in later life. The present study assessed cardiometabolic risk factors and early indicators of vascular dysfunction in adolescents from a low socio-economic rural area in South Africa. Design: Cross-sectional cohort study. Setting: The study was conducted in public schools in Mthatha, OR Tambo district municipality, Eastern Cape Province, South Africa. Participants: A total of 244 adolescents (188 females) of African ancestry aged 13–16 years were enrolled. Primary and secondary outcome measures: Anthropometric and haemodynamic measures and pulse wave velocity (PWV) were related to overweight/obesity and hypertension. Blood markers of cardiometabolic syndrome were assessed as well as vascular function (via PWV). Results: One-third (33.0%) of the adolescents exceeded the age and sex-specific body mass index percentiles for overweight (≥85th) or obesity (>95th) with a prevalence of 61.1% pre-hypertensives in this group. Overweight/obesity and hypertension were associated with higher triglycerides (lean:overweight: 0.79<1.01 mmol/L; normotensive:hypertensive: 0.82<0.89 mmol/L). Fasting glucose was higher in hypertensive as compared to normotensive adolescents (4.85>4.69 mmol/L, p<0.05). PWV was elevated in 25.9% of the children and significantly correlated with asymmetric dimethylarginine and systolic blood pressure (p<0.001). Conclusion: Overweight/obesity and hypertension show a high prevalence in rural South African youth. Almost half of the studied adolescents are at risk for developing CVD. The high association between cardiometabolic risk factors and PWV further suggests that hypertension in adolescents may promote the progression of CVD in adulthood. Early detection of those at risk and the implementation of preventive strategies in underprivileged young people is urgently needed to stop the progression of vascular damage and manifestation of CVD in rural African children.